2020
DOI: 10.12688/f1000research.23543.1
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in pregnancy: What do we really know?

Abstract: Coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), continues to escalate worldwide and has become a pressing global health concern. This article comprehensively reviews the current knowledge on the impact of COVID-19 over pregnant women and neonates, as well as current recommendations for their management. We also analyse previous evidences from viral respiratory diseases such as SARS, Middle East respiratory syndrome, and influenza that may he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 106 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…It is also known that pregnant women are vulnerable to infectious diseases that can cause both maternal and foetal adverse outcomes, compared to their non-pregnant counterparts [6]. The recent reports showed that the clinical presentation of COVID-19 among pregnant women is similar to the general population with an increased risk of pregnancy and foetal adverse outcomes such as preterm delivery, foetal distress and low birth weight [7]. The reports from recent studies have found an increased incidence of neonatal pneumonia, cases of vertical transmission to the foetus, and postpartum infections to mothers and their babies [8]- [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that pregnant women are vulnerable to infectious diseases that can cause both maternal and foetal adverse outcomes, compared to their non-pregnant counterparts [6]. The recent reports showed that the clinical presentation of COVID-19 among pregnant women is similar to the general population with an increased risk of pregnancy and foetal adverse outcomes such as preterm delivery, foetal distress and low birth weight [7]. The reports from recent studies have found an increased incidence of neonatal pneumonia, cases of vertical transmission to the foetus, and postpartum infections to mothers and their babies [8]- [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, placentas from women with confirmed SARS-CoV during the third trimester show increased intervillous or subchorionic fibrin, which is associated with impaired placental blood flow due to respiratory disease associated with hypoxia [15]. Infant outcomes of convalescent women infected with SARS-CoV during the third trimester include fetal growth restriction and small gestational age [16]. Therefore, there is concern regarding adverse pregnancy and infant outcomes due to intrauterine transmission of infection to the fetus from mothers with confirmed COVID-19.…”
Section: Zeng Et Al Emphasized That the Newborn May Developmentioning
confidence: 99%
“…This virus has a genome that is about 30,000 nucleotides (27–32 kb) and encodes structural and accessory proteins [42] . SARS-CoV preserves 79% and 50% of its genetic sequence with MERS and SARS-CoV-1, two other coronaviridae viruses, respectively, and attaches to ACE2 as the receptor for cell infection [43] . According to a large body of evidence, COVID-19 infection causes multi-organ dysfunction in the lung, heart, brain, large intestine, kidneys, and spleen compared to other coronaviruses that are only concerned with respiratory infections express the ACE2 receptor [43] , [44] , [45] , [46] , [47] , [48] .…”
Section: Covid-19mentioning
confidence: 99%